2022
DOI: 10.1073/pnas.2119318119
|View full text |Cite
|
Sign up to set email alerts
|

Foster care leads to sustained cognitive gains following severe early deprivation

Abstract: This study examined longitudinal data from the Bucharest Early Intervention Project, a randomized controlled trial of foster care as an alternative to institutional care following exposure to severe psychosocial deprivation. We report data from 135 participants assessed in early adulthood (age 18 y). We find that 16 y after randomization occurred, those who had been randomized to high-quality foster care had significantly higher IQ scores (9 points, 0.6 SD) than those randomized to care as usual. Mediation ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…Because of the need to translate the WISC-IV into Romanian for this study, a policy was implemented whereby substitutions for subtests by a supplemental test were used if participants achieved a standard score of less than 5 on the original subtest. When both an original unspoiled subtest and a supplemental subtest in the same domain were administered, the subtest with the highest score was used to estimate the FSIQ score [for more details about this "benefit of the doubt" approach to scoring, see (75)]. Five participants were identified by BEIP staff as too cognitively impaired to participate in the WISC-IV; these participants' scores were imputed to 40.…”
Section: Cognitive Abilitymentioning
confidence: 99%
“…Because of the need to translate the WISC-IV into Romanian for this study, a policy was implemented whereby substitutions for subtests by a supplemental test were used if participants achieved a standard score of less than 5 on the original subtest. When both an original unspoiled subtest and a supplemental subtest in the same domain were administered, the subtest with the highest score was used to estimate the FSIQ score [for more details about this "benefit of the doubt" approach to scoring, see (75)]. Five participants were identified by BEIP staff as too cognitively impaired to participate in the WISC-IV; these participants' scores were imputed to 40.…”
Section: Cognitive Abilitymentioning
confidence: 99%
“…These findings suggest that individual differences in caregiving quality that foster children receive is an important factor underlying the positive development of previously institutionalized children. These findings have important policy implications: training foster parents in sensitive parenting could lead to improvements not only in the social domain, but in the cognitive domain as well (Fisher et al., 2016; Humphreys et al., in press; Korom et al., 2021; Lind et al., 2017; 2020; 2021).…”
Section: Discussionmentioning
confidence: 97%
“…With few exceptions (summarized later), the intervention was largely successful in improving the developmental outcomes of children. For example, at the behavioral level, children randomly assigned to foster care showed improvements in IQ; indeed, through age 18 there was a consistent 7- to 9-point advantage in full-scale IQ in foster care compared with care as usual (see Humphreys et al, 2022). There were also improvements in language (Humphreys et al, 2020; Windsor et al, 2011), attachment security (Smyke et al, 2010), and peer relationships (Almas et al, 2015).…”
Section: Efficacy Of the Interventionmentioning
confidence: 99%
“…A follow-up of a randomized controlled trial that found children in foster care had significantly fewer externalizing symptoms and disorders, particularly true of those who remained in stable placements. Humphreys, K. L., King, L. S., Guyon-Harris, K. L., Sheridan, M. A., McLaughlin, K. A., Radulescu, A., Nelson, C. A., Fox, N. A., & Zeanah, C. H. (2022). (See References).…”
Section: Recommended Readingmentioning
confidence: 99%